IFNα and 5-Aza-2’-deoxycytidine combined with a dendritic-cell targeting DNA vaccine alter tumor immune cell infiltration in the B16F10 melanoma model - Gordy, James T.; Sandhu, Avinaash K.; Fessler, Kaitlyn; Luo, Kun; Kapoor, Aakanksha R.; Ayeh, Samuel K.; Hui, Yinan; Schill, Courtney; Chen, Fengyixin; Wang, Tianyin; Karanika, Styliani; Sunshine, Joel C.; et al. (Frontiers in Immunology, 2023)
DNA vaccines containing a fusion of the gene encoding chemokine MIP-3α (CCL20), the ligand for CCR6 on immature dendritic cells (DCs), to melanoma-associated antigen genes have enhanced anti-tumor immunity and efficacy compared to those lacking the chemokine gene. Previous work has shown that type-I interferon (IFNα or IFN) and 5-Aza-2’-deoxycytidine (5Aza) significantly enhance the therapeutic benefit of DNA vaccines vis-à-vis reduced tumor burden and improved mouse survival. Here, we explored the intratumoral immune correlates underlying the therapeutic benefit of this combination regimen (vaccine, IFN, and 5Aza) as compared to vaccine alone and IFN and 5Aza without vaccine, focusing on chemokine production and inflammatory cellular infiltration into the tumor microenvironment (TME). The combination group significantly upregulated intratumoral mRNA expression of key immune infiltration chemokines XCL1 and CXCL10. Flow cytometric analyses of tumor suspensions exhibited greater tumor infiltration of CD8+ DCs, CCR7+ DCs, and NK cells in the combination group, as well as reduced levels of myeloid-derived suppressor cells (MDSCs) in vaccinated groups. The mice receiving combination therapy also had greater proportions of effector/memory T-cells (Tem), in addition to showing an enhanced infiltration of Tem and central memory CD8+ T-cells, (Tcm). Tem and Tcm populations both correlated with smaller tumor size. Immunohistochemical analysis of tumors confirmed that CD8+ cells were more abundant overall and especially in the tumor parenchyma with combination therapy. In conclusion, efficient targeting of antigen to immature DCs with a chemokine-fusion vaccine offers a potential alternative approach to classic and dendritic cell-based vaccines. Combining this approach with IFNα and 5Aza treatments significantly improved vaccine efficacy. This treatment creates an environment of increased inflammatory chemokines that facilitates the trafficking of CD8+ DCs, NK cells, and CD8+ T-cells, especially memory cells, while reducing the amount of MDSCs. Importantly, in the combination group, CD8+ cells were more able to penetrate the tumor mass in addition to being more numerous. Further analysis of the pathways engaged by our combination therapy is expected to provide additional insights into melanoma pathogenesis and facilitate the development of novel treatment strategies.